Drivers of Decline in Diarrhea Mortality Between GEMS and VIDA Studies. (19th April 2023) - Deichsel, Emily L; Powell, Helen; Troeger, Christopher; Hossain, M Jahangir; Sow, Samba O; Omore, Richard; Jasseh, Momodou; Onwuchekwa, Uma; Obor, David; Sanogo, Doh; Jones, Joquina Chiquita M; Nasrin, Dilruba; et al.
Abstract: Background: Statistical modeling suggests that decreasing diarrhea-associated mortality rates in recent decades are largely attributed to improved case management, rotavirus vaccine, and economic development. Methods: We examined data collected in 2 multisite population-based diarrhea case-control studies, both conducted in The Gambia, Kenya, and Mali: the Global Enteric Multicenter Study (GEMS; 2008–2011) and Vaccine Impact on Diarrhea in Africa (VIDA; 2015–2018). Population-level diarrhea mortality and risk factor prevalence, estimated using these study data, were used to calculate the attribution of risk factors and interventions for diarrhea mortality using a counterfactual framework. We performed a decomposition of the effects of the changes in exposure to each risk factor between GEMS and VIDA on diarrhea mortality for each site. Results: Diarrhea mortality among children under 5 in our African sites decreased by 65.3% (95% confidence interval [CI]: –80.0%, −45.0%) from GEMS to VIDA. Kenya and Mali had large relative declines in diarrhea mortality between the 2 periods with 85.9% (95% CI: −95.1%, −71.5%) and 78.0% (95% CI: −96.0%, 36.3%) reductions, respectively. Among the risk factors considered, the largest declines in diarrhea mortality between the 2 study periods were attributed to reduction in childhood wasting (27.2%; 95% CI: −39.3%, −16.8%) and an increased rotavirus vaccine coverage (23.1%; 95% CI: −28.4%, −19.4%), zinc for diarrhea treatment (12.1%; 95% CI: −16.0%, −8.9%), and oral rehydration salts (ORS) for diarrhea treatment (10.2%). Conclusions: The VIDA study sites demonstrated exceptional reduction in diarrhea mortality over the last decade. Site-specific differences highlight an opportunity for implementation science in collaboration with policymakers to improve the equitable coverage of these interventions globally. Abstract : We demonstrated exceptional reduction in diarrhea mortality over a decade. Among the risk factors considered, the largest declines in diarrhea mortality were attributed to reduction in childhood wasting and an increased rotavirus vaccine coverage, zinc, and oral rehydration salts for diarrhea treatment.